The first report on the occurrence of twins in a freshwater crayfish, Pacifastacus leniusculus (Decapoda, Astacoidea) - Harlioglu, MM (Polish Acad of Sciences, 2002)
Twin stage 1 juveniles from the signal crayfish, Pacifastacus leniusculus, were observed in this study. No such observations have been found in the literature. The twins consist of two stage 1 juveniles that are fused at the head. Each juvenile has a separate abdomen and thorax and has the appropriate number of appendages and a telson, all characteristic of a normal stage 1 juvenile.
Keywords: twins; signal crayfish; Pacifastacus leniusculus